Pengaruh Produk Domestik Regional Bruto Sektoral Terhadap Ketimpangan Pendapatan di Indonesia - Dian Nora Herlina; Bagus Adhitya; Hari Winarto; Heris Kencana; Agus Prabawa (Majalah Imiah Manajemen & Bisnis, 2022)
The purpose of this study is to analyze the effect of GRDP in the primary, secondary and tertiary sectors on income inequality in Indonesia in 2010-2020. The locations in this study are 33 provinces in Indonesia. The research method used is multiple linear regression panel data. The results of this study are the GRDP of the primary sector has a significant negative effect on income inequality in Indonesia, the GRDP of the secondary sector has a significant positive effect on income inequality in Indonesia, while the GRDP of the tertiary sector has no effect on income inequality in Indonesia